Applying Geochemistry to Investigate the Occurrence of Riverbank Inducement into a Shallow Aquifer in Southeastern Wisconsin - (:unkn) unknown (My University, 2013)
Increased urbanization in southeastern Wisconsin has led to significant drawdown in both the shallow and deep aquifer. In Waukesha County combined radium activity levels exceeding the limit set forth by the USEPA have been detected within the deep aquifer. This has prompted the community to consider alternative, long term, drinking water supply solutions. One possible solution is riverbank inducement (RBI), in which river water is induced into the adjacent aquifer as recharge. This would make the shallow aquifer an effective addendum to growing water supply demands, and reduce the effects of excessive pumping. Using basic geochemical analyses, this study examines the interaction between surface water and shallow groundwater along a segment of the Fox River in Waukesha County, with consideration given to mixing, chemical evolution and travel time. In 2007 a network of sampling sites was established to monitor the chemistry of treated waste-water effluent, river water and municipal wells located in close proximity to the river. Increases in groundwater chloride concentrations over time suggest that the shallow aquifer is susceptible to sodium chloride inputs from three upstream waste water treatment plants, road salt application and water softeners. Multiple lines of evidence are used to determine the occurrence of RBI, including major ion chemistry, trace elements and stable isotope signatures. Modeling, using the aqueous geochemical program PHREEQC, is used to determine the processes occurring under a RBI scenario and to explain the chemical evolution observed in groundwater. Trace element analysis is performed to discriminate between waste water effluent and road salt as the main source of sodium chloride. PHREEQC results indicate that 35% to 40% of groundwater is induced from the river. In addition, the travel time between the river and the wells is estimated to take approximately 2 years, furthering our understanding of groundwater pathways. These results are supported by previous numeric flow modeling, using MODFLOW, and electromagnetic surveys. Trace element analysis suggests that waste water effluent is the primary source of contamination. The results from preliminary stable isotope analyses are also included to show the isotopic signatures of the different waters and the effects of mixing.
Keywords: Riverbank Inducement; Sodium Chloride; Tracers